2014
DOI: 10.4168/aair.2014.6.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Offending Allergens of Allergic Rhinitis According to Age: Optimization of Skin Prick Test Allergens

Abstract: PurposeThis study evaluates offending allergens in patients with allergic rhinitis (AR) according to age that establish a minimal panel for skin prick test (SPT) allergens required to identify if a patient is sensitized.MethodsWe retrospectively analyzed SPT results according to age to determine the minimum test battery panel necessary to screen at least 93%-95% of AR patients. Allergic skin tests (common airborne indoor and outdoor allergens) were performed on 7,182 patients from January 2007 to June 2011. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
37
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 7 publications
7
37
0
3
Order By: Relevance
“…To overcome this limitation and improve accuracy, this study reestimated the prevalence of AR by multiplying it with the reciprocal of the D farinae frequency, which is the best choice to improve accuracy because it has the highest frequency (76.4%) among all indoor and outdoor allergens in Korea. 13 The prevalence was slightly elevated to 18.5% on reestimation but was still much lower than the symptom-based prevalence of 27.6%. This reestimated prevalence still has a limited value because KNHANES measured specific IgE, yet the frequency was calculated using the skin prick test.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…To overcome this limitation and improve accuracy, this study reestimated the prevalence of AR by multiplying it with the reciprocal of the D farinae frequency, which is the best choice to improve accuracy because it has the highest frequency (76.4%) among all indoor and outdoor allergens in Korea. 13 The prevalence was slightly elevated to 18.5% on reestimation but was still much lower than the symptom-based prevalence of 27.6%. This reestimated prevalence still has a limited value because KNHANES measured specific IgE, yet the frequency was calculated using the skin prick test.…”
Section: Discussionmentioning
confidence: 78%
“…Allergic rhinitis was divided into (1) seasonal or perennial AR according to symptom seasonality and (2) intermittent mild or intermittent moderate to severe, persistent mild, or persistent moderate to severe AR according to the Allergic Rhinitis and its Impact on Asthma (ARIA) guideline. 4 To improve the accuracy of AR prevalence, we used a previous study 13 concerning the allergen frequency in a skin prick test. Dematophagoides farinae has the highest frequency in Korean allergy patients: 83.8% for those aged 7 to 12 years, 78.5% for those aged 13 to 19 years, 91.5% for those aged 20 to 29 years, 80.7% for those aged 30 to 39 years, 66.9% for those aged 40 to 49 years, 58.8% for those aged 50 to 59 years, 55.3% for those aged 60 to 69 years, and 58.8% for those older than 70 years.…”
Section: Allergic Rhinitismentioning
confidence: 99%
See 1 more Smart Citation
“…Existing guidelines are based on patients outside of Korea; therefore, the minimum test battery of 18 inhalant allergens ( Dermatophagoides pteronyssinus and Dermatophagoides farinae , Cat and Dog dander, Artemisia , Blatella , Alternaria , Parietaria , Ambroisia , Aspergillus , Cladosporium , Grass, Cypress-, Olive-, Birch-, Alder-, Plane-pollen, and Hazel) advocated by the Global Allergy and Asthma European Network would not be relevant in Korean patients 12. In Korea, particular pollens, including Japanese hop ( Humulus japonicas ) or Japanese Cedar ( Cryptomeria japonica ) have been reported as the major pollens of AR in south provinces 1314. Furthermore, offending allergens are significantly different according to age, variability of offending allergens from indoor allergens in early childhood to outdoor allergens in late childhood 14.…”
Section: Discussionmentioning
confidence: 99%
“…Japanese Cedar is the most common allergen in Japan. House dust mites (HDM) comprised the larger proportion of sensitized allergens among the younger compared with the older age groups in Korea 14. A recent Chinese study found that HDMs were the major allergen affecting patients; in addition, patients in northern China showed significantly greater sensitization to pollens than did those from the other regions 16.…”
mentioning
confidence: 99%